1960
DOI: 10.1021/jo01080a026
|View full text |Cite
|
Sign up to set email alerts
|

Unique Fatty Acids from Limnanthes douglasii Seed Oil: The C20- and C22-Monoenes2

Abstract: perature for several days 3.8 g. of crude crystalline material was deposited. This was chromatographed on a Florisil column using benzene as solvent. The benzene eluates gave 1.4 g. of a monohydroxy sapogenin. This material (0.2 g.) was refluxed for 30 min. in 5 ml. of acetic anhydride in pyridine (1:1). The solution was evaporated to dryness in vacuo and the residue recrystallized from methyl alcohol to give needles, m.p. 194-197°. These crystals were identified as yamogenin acetate by comparison of its infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

1966
1966
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…The seed oil of meadowfoam is a rich source of novel very long-chain fatty acids (C 20 and C 22 ) (Smith et al 1960;Bagby et al 1961). The oil has unusually high concentrations of D5 unsaturated (typically 86%) and C 20 and C 22 (typically 96%) fatty acids and extraordinarily low concentrations of saturated fatty acids (typically less than 2%) (Knapp and Crane 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The seed oil of meadowfoam is a rich source of novel very long-chain fatty acids (C 20 and C 22 ) (Smith et al 1960;Bagby et al 1961). The oil has unusually high concentrations of D5 unsaturated (typically 86%) and C 20 and C 22 (typically 96%) fatty acids and extraordinarily low concentrations of saturated fatty acids (typically less than 2%) (Knapp and Crane 1995).…”
Section: Introductionmentioning
confidence: 99%
“…The triacylglycerol fraction of the mature seed is composed principally of 20: 1 (Sc), 22:1(13c), and 22:2(5c13c) fatty acids (13,20). Our interest in this plant seed stems from the fact that the developing seed contains the enzymes necessary for the biosynthesis of C20 and C22 acids.…”
mentioning
confidence: 99%
“…[1-'4C]Linoleic acid was also tested in vivo, and label was incorporated into triacylglycerols (3.5%). This fraction contained labeled 18:2(9c12c) (20%1o), 20 for 10% of the total label, which can be assumed to reside exclusively in C( 1), as previous studies have shown that this isomer is produced by elongation of oleate (5,15,17). If the biosynthesis of 20:1(5c) occurs via an elongation of preformed palmitate, the ozonolysis data can be used to calculate that 34% of the total 14C in the 20:1 fraction resides in C(5) to C(19) of the A5 cis isomer, with 28% each in C(l) and C(3).…”
mentioning
confidence: 99%
“…Meadowfoam is a rich source of unique unsaturated long-chain fatty acids (LCFAs), in particular cis-5 unsaturated FAs (20:1Δ5, 22:1Δ5 and 22:2Δ5Δ13). Meadowfoam seed oil thus contains some 95% of FAs with chain lengths of 20 carbon atoms or longer (C20 and C22 monoenes and dienes) [98]. The unique chemistry of meadowfoam (SFA 1.0%, MUFA 82.0%, PUFA 17.0%) has stimulated its development as an industrial oilseed crop [99].…”
Section: Non-edible Oilseeds For Lubricantsmentioning
confidence: 99%